THE DIFFERENCE CHANGE IN WEIGHT FAMILY PLANNING INJECTION ACCEPTORS THREE MONTHS WITH ONE MONTH IN MUARA VILLAGE CIREBON DISTRICT - Dwi Lestari Anugerahwati (PT. Jurnal Center Indonesia Publisher, 2024)
Injected contraception is the most contraception method chosen by Indonesian women. There are 2 types of injected contraception, 3 monthly injecion which consists of progesterone only and 1 monthly injection consists of a combination of oesterogen-progesterone. One of its side effect is increase weight, which is usually distressing for women due to the increase risk of suffering from many diseases such as heart attack, type-2 diabetes mellitus, sleep apnea, certain cancer, osteoarthritis, and asthma. The study aim was to identify the difference weight gain occurence between 3 monthly and 1 monthly injected contraception users in Muara Village- Suranenggala District. This research method uses comparative analytic studies using cross sectional resulting research which measured in interval scale. The sample is all 3 months KB injecting participants as much as 30 respondents and 1 month KB injections as much as 30 respondents. The data is analysis using t-test. The result showed a ρ value of 0,005 which meant there was a difference in weight gain occurence between the users of 3 monthly and 1 monthly injected contraception. The 3 monthly injection had been proven increasing the incidence of weight gain compared to the 1 monthly one. It was suggested that midwives should give proper counselling regarding to side effect of increasing weight gain during the use of 3 monthly contraceptive injection to be aware of by the users. Further investigation on other influencing factors of weight gain among contraceptive injection users.